Assessment of Dog Owner Concern Regarding Peri-operative Nausea and Vomiting and Willingness to Pay for Anti-emetic Treatment - Kraus, Bonnie L. Hay; Cazlan, Callie (Frontiers in Veterinary Science, 2019)
Objective: The objective of this study was to assess dog owner’s concern regarding peri-operative nausea and vomiting and their willingness to pay (WTP) for treatment. Design: Descriptive Survey. Sample: A survey was administered to 104 dog owning clients with non-emergent surgical (52) or non-surgical (52) appointments. Procedure: Descriptive statistics were calculated. A Spearman’s Rank Co-efficient was used to correlate predictive data. Results: Ninety-seven (93%) dog owners had at least some worry regarding their dog experiencing nausea associated with opioid analgesics and anesthesia with 39/104 (37.5%) moderately to very worried. Forty-one owners (39%) would definitely and 59/104 (56.7%) would likely choose treatment to decrease or prevent signs of nausea. Ninety-four owners (90.4%) had at least some worry regarding vomiting and 48/104 (46%) indicated they were moderately to very worried. Fifty-three owners (51.4%) would definitely and 49/103 (47.6%) would likely choose treatment to prevent vomiting. The median and mean amount owners were willing to pay was $50 and $75 respectively. Ninety-five (91.3%) were likely or very likely to opt for treatment if required to arrive one hour earlier for their appointment. There was no correlation between age, income, or owner’s PONV experience with likelihood of choosing treatment but there was a significant positive correlation with the owner’s level of education. Conclusion: Canine owners are concerned with their pets experiencing nausea and vomiting in relation to opioid analgesics and anesthesia and are willing to pay and stay the required time for effective treatment.